(untitled) (Challenges of the Future, 2021)
Background and Originality: The purpose of the research is to identify the challenges surrounding predatory journals; examine what predatory journals are and what are the risks associated with predatory magazines. We are interested in the opinions of various authors regarding predatory journals. The article provides insight into the research of various authors; presents the background of the phenomenon of predatory journals in the literature review, and presents and compares three areas in the results; definition of predatory journals, who publishes and why in predatory journals and what is the impact of predatory journals on science. The review covers current literature of the last five years. Method: The research is based on a review of existing data. We searched for articles on Google Scholar. We used the keywords in Table 1 to search until data saturation. Using the predetermined keywords, we found a total of 46 articles. To review the literature, we selected articles published from 2015 onwards. We used only articles relating to predatory journals and excluded those relating to hijacked journals or pseudo-journals. We excluded those articles that do not comment on the content of predatory journals/publishers; do not assess the impact of predatory journals on science; do not state who publishes or why they publish in predatory journals. After filtering, we used 30 articles to compare different authors’ views on predatory journals, the results on who publishes in predatory journals, and the impact of predatory journals on science in relation to different authors. The results were presented in the form of tables according to each research question. The results’ reliability was checked by intra-rater reliability; the review was performed at two separate time points seven days apart. There are no differences between the first and second intra-rater reliability. Key findings were made by inductive reasoning. Results: All authors from the literature review take a concrete position on predatory journals. The existence of predatory journals with the aim of making money is especially emphasized - the authors describe them as dishonest, not transparent, exploitative, and fraudulent. They point to the lack of clearly defined criteria for placing a journal on the list of predatory journals. Authors and their reasons for publication in predatory journals can be divided into two groups: those who do not intentionally publish and those who intentionally publish. All authors state that predatory publishing has a negative impact on science. They point out that such publishing is the greatest threat to science since the Inquisition time and that the credibility of science is at stake. Society: The article contributes to understanding the importance of predatory journals and what this means for science and, consequently, society. Society is evolving in step with science - what will society develop if science is not credible and reliable? This article reveals only a few topics related to predatory journals, to which research organizations in particular need to pay attention. Above all, it is necessary to balance the pressures on authors on the principle of ‘publish or perish’ and to emphasize quality over quantity. Limitations / further research: The research is limited by focusing on the three areas highlighted. It does not delve into the authors’ geographical dispersion or into the geographical dispersion of predatory journals or into the scientific field where predatory journals are most prevalent. For further research, we could conduct an empirical study by reviewing the existing list of predatory journals and investigating where the authors come from, where the journals are located, the incidence of publications by Slovenian authors, and the like.